Agen Perubahan dalam Model Komunikasi Pemasaran Sosial Kampung Wisata - Febriani, Nufian Susanti; Tamitiadini, Dian (Jurnal Komunikasi Profesional, 2018)
This paper aims to develop an effective model of social marketing communications in the tourism village tour by utilizing green energy independently in the village as a tourist attraction. The method used to develop the model is qualitative research. Through this research we get a model of social marketing communication that can survive and sustain through the use of a change agent. To change, establish and maintain new positive behaviors that arise, an agent of change must consistently and continuously influence its target adopter until the desired goal is achieved. Subjects in this study is Glintung tourism village of East Java which has gained national recognition as a green tourist village of independent energy. Through his change agent, Glintung tourism village is able to market itself while creating green energy independently for the environment.Â Keywords: Agent of Change, Social Marketing Communications, Tourism VillageÂ